Urban environment interventions linked to the promotion of physical activity: A mixed methods study applied to the urban context of Latin America. (April 2015) - Gomez, Luis F.; Sarmiento, Rodrigo; Ordoñez, Maria Fernanda; Pardo, Carlos Felipe; de Sá, Thiago Hérick; Mallarino, Christina H.; Miranda, J. Jaime; Mosquera, Janeth; Parra, Diana C.; Reis, Rodrigo; Quistberg, D. Alex
Abstract: This study summarizes the evidence from quantitative systematic reviews that assessed the association between urban environment attributes and physical activity. It also documents sociopolitical barriers and facilitators involved in urban interventions linked with active living in the ten most populated urban settings of Latin America. The synthesis of evidence indicates that several attributes of urban environments are associated with physical activity, including land-use mix and cycling infrastructure. The documentary analysis indicated that despite the benefits and opportunities provided by the programs and existing infrastructure in the examined cities, an overall concern is the rising inequality in the coverage and distribution of the initiatives in the region. If these programs and initiatives are to achieve a real population level effect that helps to reduce health disparities, they need to examine their social and spatial distribution within the cities so they can reach underserved populations and develop to their full potential. Highlights: Most research on physical activity and the environment was in high income countries. There is an unequal distribution of supportive urban environments in Latin American. The Ciclovia program may offset urban inequalities existing in public green areas. Strong civil society leadership is needed for sustainable policy and programs.